Ensino fundamental de nove anos e possíveis implicações no processo de alfabetização : um estudo de caso - Brandão, Melissa de Oliveira Machado (2012)
The present study was developed in the research line training, political and practice in education as being linked to the research Project Continuing education of teachers of literacy and literacy in the early years of elementary school , coordinated by professor Dr.ª Cleoni Maria Barboza Fernandes. The investigation consisted of a case study, supported by authors such as Marli André (1995), and aimed to understand how the deployment is going to elementary school for nine years and its possible implications in the process of a literacy class the first years of basic education in a state school of metropolitan capital. From the qualitative methodology, continuous observation was one of the strategies for data collection, using me records of various everyday situations through a field diary, semi-structured interviews with the teacher oh the ruling class of the first year of secondary fundamental public schools. The survey was drawn from nine years of teaching, involving the concept of childhood, the processes of literacy and literacy that are being offered for children entering with six years of age in primary school and know how it happened rite of passage between kindergarten and elementary school for these subjects participated in this research, looking for alternatives so that there is a continuity in this relationship. The study was based on a theoretical as Euclides Redin, Jean Piaget, Magda Soares, Paulo Freire, Walter Kohan among others.